Combination of psycho- and pharmacotherapy as a modern method of treatment of Alzheimer’s disease - Próchnicka, Magdalena; Nowak, Dominika; Siwek, Michał; Giermasiński, Adrian; Tuszyńska, Weronika; Zarzycki, Adam; Skorupski, Bartosz; Komisarczuk, Mateusz (Journal of Education, Health and Sport, 2023)
Introduction: Alzheimer’s disease is a degenerative disease of the brain, caused by the deposition of beta-amyloid and tau protein. It is characterized by progressive memory and behavior disorders which, over time, completely prevent the patient from functioning properly in everyday life, performing work and disrupting social contacts. Communication problems arise and patients forget more and more words. Unfortunately, we are not able to completely stop the progression of this disease, but we can only delay its development. To delay the progression of the disease, pharmacotherapy includes acetylcholinesterase inhibitors and NMDA receptor antagonists. Matherials and methods: This article, based on a PubMed review of available research, examines the impact of rivastigmine, donepezil, memantine and psychotherapy on delaying disease progression. Results: A number of studies have investigated the effect of 6-12 milligrams of rivastigmine, 10 milligrams of donepezil and 20 milligrams of memantine on patients’ ability to communicate. The results were checked using the MMSE, ADAS or SIB scales and interviews conducted regularly by clinicians. In addition, patients were subjected to various forms of psychotherapy, including reminiscence therapy and cognitive therapy. All groups experienced significantly less deterioration in their functional stage of disease compared to the placebo groups. Conclusions: The best results in the treatment of Alzheimer’s disease can be obtained by combining pharmacological therapy with non-pharmacological effects. Thanks to this form of treatment, the progression of the disease is delayed, and patients retain their communication abilities for longer.